Financial constraints and firm size: Micro-evidence and aggregate implications - Miguel H. Ferreira; Timo Haber; Christian Rörig (Queen Mary University of London, School of Economics and Finance, 2023)
Using a unique dataset covering the universe of Portuguese firms and their credit situation we show that financially constrained firms are found across the entire firm size distribution, even in the top 1%. Incorporating a richer, empirically supported, productivity process into a standard heterogeneous firms model generates a joint distribution of size and credit constraints in line with the data. The presence of large constrained firms in the economy, together with their elevated capital share, explains about 66% of the response of output to a financial shock. We conclude by providing micro-evidence in support of the model mechanism.
Keywords: E62; E22; E23; 330; Firm size; business cycle; financial accelerator